Transdisciplinary knowledge co-production as a catalyst for community-led innovation: a case study of farmers’ milk cooperative in Laikipia, Kenya - Mukhovi, Stellah Mikalitsa; Kiteme, Boniface; Mwangi, John; Wambugu, Grace (Frontiers in Sustainable Food Systems, 2024)
Food systems must be reconfigured for them to alleviate poverty, hunger, food losses and wastes, promote healthy diets, inclusivity, resilience, livelihood opportunities, and to be environmentally sustainable. This requires a shift in production, consumption, as well as transformative research, responsive policy, people-centered innovations, and safety nets for the most vulnerable people. Transformation of food systems also depend on a shift in science, policy, and practice to promote sustainable futures. For science to be transformative, discipline-oriented research is important, however, societal challenges are becoming more complex hence requiring more interdisciplinary research with collaboration and integration of knowledge from actors in policy and practice. Scientists must learn to first work together, and then work with non-academic actors to solve complex problems facing food systems and the society at large. This kind of research is transdisciplinary, meaning right from the framing of complex problems, data collection, analysis, and validation, nonacademic actors must be actively involved in the process of knowledge co-creation to create sustainable outcomes. This study demonstrates how co-production of knowledge between academic and non-academic actors through a participatory negotiated process, can contribute to transformative development intervention. The study applies a case study of agro pastoral community involved in a milk value chain in Laikipia County. The transformative areas in the study were; a) capacity development in commercial dairy farming b) formation of Umande farmers' Cooperative, and c) construction of a cooler house, and installation of milk cooling system for milk bulking, and value addition. The case study offers several lessons; a) role of transdiciplinarity on science, policy, and practice, b) proper identification of stakeholders in collaborative community development initiative, c) the community must always be at the forefront of any development initiative for ownership and sustainability, and d) skills development and economic empowerment are paramount for any new innovation in the community. The objectives of the study were a) participatory assessment of local food system to identify the strength and weaknesses, b) assessment of perceived benefits of farmer capacity development and lessons learned, and c) assessment of farmer perception on the benefits of milk cooling and bulking system on livelihoods.